Electrical measurement of antiferromagnetic moments in exchange-coupled IrMn/NiFe stacks - Martí, X; Park, B G; Wunderlich, J; Reichlová, H; Kurosaki, Y; Yamada, M; Yamamoto, H; Nishide, A; Hayakawa, J; Takahashi, H; Jungwirth, T (Physical review letters, 2012)
We employ antiferromagnetic tunneling anisotropic magnetoresistance to study the behavior of antiferromagnetically ordered moments in IrMn exchange coupled to NiFe. Experiments performed by common laboratory tools for magnetization and electrical transport measurements allow us to directly link the broadening of the NiFe hysteresis loop and its shift (exchange bias) to the rotation and pinning of antiferromagnetic moments in IrMn. At higher temperatures, the broadened loops show zero shift, which correlates with the observation of fully rotating antiferromagnetic moments inside the IrMn film. The onset of exchange bias at lower temperatures is linked to a partial rotation between distinct metastable states and pinning of the IrMn antiferromagnetic moments in these states. The observation complements common pictures of exchange bias and reveals an electrically measurable memory effect in an antiferromagnet.